NEUROLOGICAL STATE IN SCHOOL-AGE CHILDREN AFTER TOTAL ANESTHESIA DURING SURGICAL OPERATIONS OF DIFFERENT DURATION (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This thesis aims to investigate the neurological outcomes in school-age children following surgical procedures performed under total anesthesia, with a focus on comparing the effects of short-duration versus long-duration surgeries. The key objectives are:To assess the incidence of new-onset neurological deficits, such as motor, sensory, and cognitive impairments, in children after undergoing short-duration (less than 4 hours) versus long-duration (4 hours or more) surgical interventions.